2017
DOI: 10.1108/er-03-2017-0071
|View full text |Cite
|
Sign up to set email alerts
|

The living wage as an income range for decent work and life

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 32 publications
1
38
0
5
Order By: Relevance
“…In conclusion, our initial findings in South Africa (and New Zealand) are consistent with poverty theory which states that employees earning below a certain threshold are trapped in poverty (Carr et al 2016). Moreover, there was a threshold range (Yao et al 2017). Below this range, workers feel trapped in working poverty, while above it there was a transformation not only in quality of work life but also in job attitudes and other human factors linked to productivity.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…In conclusion, our initial findings in South Africa (and New Zealand) are consistent with poverty theory which states that employees earning below a certain threshold are trapped in poverty (Carr et al 2016). Moreover, there was a threshold range (Yao et al 2017). Below this range, workers feel trapped in working poverty, while above it there was a transformation not only in quality of work life but also in job attitudes and other human factors linked to productivity.…”
Section: Introductionsupporting
confidence: 87%
“…The research team in Thailand joined Project GLOW in 2017 and sought to explore the meaning of living wage in Thailand. Researchers have been exploring the meaning and application of living wage in diverse contexts; for this research the definition given by Yao et al (2017) set the direction as it explained it as a wage level that is perceived by employees as a "step change" for enhancement in work-related and overall wellbeing. Rooting the research in the context of local culture, the research team investigated if the living wage could be examined from the lens of applying the SEP, which was developed by the late King Bhumibol Adulyadej in 1997.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, attention has been directed from minimum pay to "decent" or living wages, which focus on enabling quality of life and work life rather than merely securing economic subsistence (Carr et al, 2016). While a number of studies have shown beneficial effects of such living wages on workers' capabilities (Sen, 1999), little is known about how increased income translates into capability development (Carr et al, 2018;Parker et al, 2016;Yao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…An intellectual context for this paper is the continuing debate between advocates of growth through everyday wages that are lower, versus higher [9]. Much of the available evidence remains inconclusive to either side, partly perhaps because it tends to rely on single data points (i.e., a specific living wage figure), rather than a variable (multiple wage values along a wage spectrum): As we have argued elsewhere, in theory the living wage is an empirically determinable point of inflexion, or pivot from along a wage and income continuum, where wage covers not only the material cost of living, such as food and shelter, but also one's quality of living, including quality of work life [10,11]. Setting "a" living wage is thereby important towards creating the possibility of escaping from working poverty traps, and for cultivating climates of work justice and work-life balance [12,13].…”
Section: Introductionmentioning
confidence: 99%